The effect of diamond toothpastes on surface gloss of resin composites - Mathias-Santamaria, Ingrid Fernandes [UNESP]; Roulet, Jean-Francois (My University, 2019)
Purpose: To evaluate the effect of diamond toothpastes on the gloss surface of five resin composites. Methods: 30 discs of each resin composite in A2 shade [Filtek Supreme Ultra (FS), Tetric EvoCeram (TE), IPS Empress Direct (ED), Charisma (CC), Venus Diamond (VD)] were made. The samples were divided into three groups according to the toothpaste: Colgate Total Clean Mint (control) (CTC), Candida White Diamond (CWD) and Emoform-F Diamond (EFD). After standardized polishing, the samples were brushed using a toothbrushing simulator, and gloss measurements were assessed at baseline and 15, 30, 45, 60, 75, 90, 105 and 120 minutes. Results: Diamond toothpastes behaved differently from each other: the CWD and CTC groups presented the lowest values compared to EFD (P< 0.05). Nanofilled composites presented higher gloss values than other composites when brushed with various toothpastes (P< 0.05). The addition of diamond particles as abrasives in toothpastes can affect resin composites' surface gloss.